Escola do Novo Tempo: o ensino de período integral no estado de Rondônia, uma parceria público-privada (de 2017 a 2022) - Musiau, Paulo Malicka (Universidade do Vale do Rio dos Sinos, 2025)
This study is the result of research on the public-private relationship established between the State of Rondônia and the Institute of Co-responsibility for Education (ICE), as well as the effects that such a partnership generates in the context of Secondary Education after the arrival of the School of Choice Model. Within this thematic context, the research aims to identify the structuring principles of the School of Choice Model, in order to understand the articulations of this model in connection with neoliberal rationality and with the possible production of a characteristic school culture, in the State of Rondônia, between 2017 and 2022. The methodology used focuses on the Comprehensive Interview, through interviews with managers and teachers, as well as on the analysis of official documents of the New Time School Program in the State of Rondônia, in 2017. Thus, through the analysis of such interviews and the analysis of the ICE Training Notebooks, it was possible to understand that the full-time school program arouses, in managers, teachers and students, a certain culture, which is identified through the daily practices developed in the school context and in the relationship between strategy and tactics, produced in this context and understood from Michel de Certeau (1996). The school culture observed in this Program concerns some procedures carried out by the actors involved, such as: carrying out planning at school, as it is a requirement of the Program; preparing an Elective, with the aim of meeting the students' desires; acting as a tutor, sometimes during lunch or planning time; having a weekly agenda, which includes an area meeting, with the purpose of aligning and becoming aware of the activities proposed by the school management and other areas; focusing on the weekly evaluation, with a view to profitable and satisfactory results that satisfy the interests of ICE and the State Department of Education, which directly interferes in the pedagogical movements of teachers, through standardized evaluations, conditioning teachers and students to meet the demands required by the agencies responsible for basic education in the country. In light of this scenario, I defend the thesis that the New Time School Program, inspired by the School of Choice Model, presents ideological elements present in the Training Notebooks that are used by the Institute of Co-responsibility for Education to raise, in school management, in teachers and students, a culture, in certain aspects, unique to this school model. Such a model is based on a business managerialism, which prepares students to meet the desires of the labor market and conditions them to a neoliberal rationality, through a discourse of becoming self-entrepreneurs. In this sense, they will be responsible for their successes and failures, which exempts the State from its responsibility for education, in a public-private partnership that has systematically advanced in Brazilian basic education in recent years.
Keywords: Escola da Escolha; Relação público-privada; Ensino Médio; Currículo; Práticas cotidianas; Cultura escolar; School of Choice; Public-private relationship; High School; Curriculum; Everyday practices; School culture; ACCNPQ::Ciências Humanas::Educação